Mucoadhesive assessment of different antifungal nanoformulations. (8th August 2018) - Roque, L; Alopaeus, J; Reis, Claudia; Rijo, P; Molpeceres, J; Hagesaether, E; Tho, I; Reis, Catarina
Abstract: Oral candidiasis is an important opportunistic fungal infection and polyenes and azoles are still the most used antifungal agents. However, the oral absorption resulting from most available treatments is generally poor and, consequently, a very high frequency of administrations of antifungal agents is strongly required. Therefore, the major challenge is to improve the retention of the antifungal agents in buccal mucosa, and the encapsulation into mucoadhesive systems may be considered as a possible strategy to achieve this objective. Three types of mucoadhesive polymeric nanoparticles (polylactic acid (PLA), polylactic-co-glycolic acid (PLGA) and alginate) were prepared using nystatin as model drug. The drug-loaded nanoparticles were then included in toothpaste, oral gel and oral films, respectively. The results demonstrated that the loaded nanoparticles were successfully produced, presenting a mean size between 300–900 nm and with a negative surface charge. Also, the determination of the encapsulation efficiency of all nanoparticles showed values above 70%. In terms of the in vitro mucoadhesion, the best formulation was the oral film loaded with the PLGA nanoparticles followed by the oral gel with PLA nanoparticles and thirdly the toothpaste with alginate nanoparticles. This was confirmed in an in vitro rinsing model with mucus producing HT29-MTX cells, where the percentage of nystatin retained to the cells after 40 min of simulated saliva flow was between 10–27% when formulations were used and only 4% for free nystatin. Further studies will include in vivo testing using animal models.